Punishing the Poor? Child Welfare and Protection under Neoliberalism - Anna Gupta (Social Work and Society, 2019)
In contemporary England the involvement of the state in private family life has undergone a significant shift in tone and substance, with this being played out in authoritarian child protection (CP) interventions. At the same time as cuts to welfare and support services are increasing hardship for families, the numbers of CP investigations and children in care are rising. In this presentation it is argued that a 'perfect storm' ensued from the coming together of 'child-focussed' early intervention within a social investment rationale of New Labour and an acceleration of neoliberal policies under subsequent Conservative-led Governments. The Capability Approach (CA), it is argued, can inform a critical analysis of child protection policy and practice and provide a framework for ethical practice. However, it is also suggested that the CA can be strengthened by drawing on the work of critical sociologists, such as Loic Wacquant to understand what is happening to the poorest children and families and their communities in 'austerity' England. The presentation concludes with ideas about a social model of CP that addresses social determinants of harm to children and families, and promotes their flourishing.